Hard work paid off for UMPSA international graduates from 14 countries - Khairul Amri, Abdul Aziz; Jamilah Bebe, Mohamad (UMPSA, 2023)
GAMBANG, 21 October 2023 – 81 international graduates from 14 countries celebrated their success in completing their studies in the 18th Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Convocation Ceremony held on 21st to 24th November 2023 in UMPSA Gambang Campus.